360-Degree Rhetorical Analysis of Job Hunting: A Four-Part, Multimodal Project. Issue 2 (June 2013) - Ding, Huiling; Ding, Xin
This article proposes the use of a four-component multimodal employment project that offers students a 360-degree understanding of the rhetorical situations surrounding job searches. More specifically, we argue for the use of the four deliverables of written resumes and cover letters, mock oral onsite interview, video resume analysis, and peer critique of social media profiles in a widely taught employment project to help students better analyze the complicated rhetorical situations surrounding job applications and to facilitate better peer collaboration and serious revision of the two high-stakes documents of cover letters and resumes.